Pengembangan Usahatani Tanaman Singkong di Lahan Smkn 1 Borong Kabupaten Manggarai Timur - Kaleka, Marten Umbu; Coo Lea, Victoria (Jurnal MeA (Media Agribisnis), 2024)
The establishment of the cassava agribusiness business owned by SMKN 1 Borong is the result of a learning program that uses a production/service-based learning model, or factory-based learning, to educate students and prepare participants to face the world of industry and the world of work by improving their skills and competencies before students enter working world. The aim of the research is to produce recommendations for cassava cultivation guidelines in the Department of Food Crops and Horticulture at SMKN 1 Borong and to determine the feasibility of cassava farming at SMKN 1 Borong. The results of this research were reported to the Astra Education Foundation as the owner of the Borong 1 State Vocational High School transformation program into a superior vocational school. The research uses qualitative and quantitative research approaches. The method for determining the location is purposive (deliberately) by considering several things. In this research, primary data from key informants was used combined with secondary data from educational institutions and other relevant sources. The data analysis used is descriptive analysis and farming feasibility analysis which includes net present value, net B/C ratio and internal rate of return. The research results show that the requirements for cassava cultivation include planting specifications, land preparation, seed and seed preparation, land processing, planting, maintenance and harvesting. The results of the farming feasibility analysis show that the net present value is Rp. 16,862,618.58, which is more than zero, the net B/C achieved is 2.03 times greater than one, and the internal rate of return is 1.39, which is higher than bank interest of 12%. used. This means that cassava cultivation is feasible.Kata Kunci: Kelayakan; Usahatani; Singkong; Borong